GUIDANCE AND COUNSELING IN SCHOOL ACCOUNTABILITY - Mita Anggela Putri; Neviyarni Neviyarni; Riska Ahmad; Yarmis Syukur (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2018)
This study discusses guidance and counseling accountability in schools so that school counselors can demonstrate their duties as instrumental personnel in achieving optimal student competencies. One model of accountability activities is the MEASURE model developed by Stone and Dahir (2016), as a six-step accountability process that helps school counselors to implement a component of accountability into counseling and guidance programs. The advice in this study is for school counselors to conduct In-Service Training to help them improve their skills in accountability.